Effectiveness of family-centered intervention programs on objectively measured physical activity in children aged under 13: a meta-analysis of randomized controlled trials - Qian Wang; Lawrence T. Lam; Heng Lin; Wenxian Yang; Fuxian Yin; Yongwei Li (Frontiers in Public Health, 2025)
IntroductionThis review aims to evaluate the efficacy of family-centered physical activity interventions, as assessed through randomized controlled trials (RCTs) on objectively measured moderate-to-vigorous physical activity (MVPA) and sedentary behavior (SB) in children under 13. To ensure higher quality and reduce measurement bias, a quantitative approach was employed.MethodsA detailed search was systematically conducted in PubMed, Medline, Web of Science, and Embase for studies published between January 2013 and February 2024. Only RCTs investigating the efficacy of family-centered interventions using objective measurements in children under 13 were included. Study characteristics were systematically summarized, and the risk of bias was assessed using the Cochrane risk of bias tool. Meta-analyses were performed to evaluate the effectiveness of interventions, and subgroup analyses were conducted in RevMan 5.4 to explore potential effects.ResultsTen studies, comprising a total of 1,557 parent-child dyads, met the inclusion criteria. The mean age of participants ranged from 3 to 11 years. The studies assessed various outcomes, including MVPA and sedentary time. Meta-analysis revealed that family-centered interventions were significantly associated with increased MVPA (WMD = 5.13, 95% CI = 1.09 to 9.17, p = 0.01). However, no significant difference in SB was found between the intervention and control groups (WMD = −2.24, 95% CI = −9.33 to 4.86, p = 0.54). Subgroup analyses showed significant effects for short-term interventions (WMD = 9.08, 95% CI = 2.54 to 15.62, p = 0.007) and on weekends (SMD = 0.63, 95% CI = 0.33 to 0.93, p < 0.05).ConclusionsFamily-centered interventions are a promising approach to enhancing children's MVPA, particularly in the short-term and on weekends. However, the effect on reducing SB appears limited. Future research should focus on larger, more diverse samples (e.g., populations in developing countries), utilize high-quality measurement tools, and novel outcomes (e.g., FMS) to better assess the effectiveness of these interventions.Trial registrationMeta-analysis PROSPERO: CRD42023488011.